The effect of practicing high-intensity interval training (HIIT) on developing general endurance and reducing body fat percentage among beginner athletes. - Ezzat, Asst.LSaif Saad; Marzina, L.Dr. Stefan Jajo; Ahmed, Asst.L. Enas Anad (Sulaimani Journal for Humanities, 2026)
The study aimed to identify the effect of practicing high-intensity interval training (HIIT) on developing general endurance and reducing body fat percentage among beginners practicing sports. The research sample consisted of 20 people practicing sports at a fitness center on the right bank of Mosul, aged between (20-30) years, and they were chosen randomly. The researchers used the general endurance test for a distance of 600m and the body fat percentage equation as means of collecting information to achieve the research objectives. As for the statistical means, the SPSS statistical program was used to reach the results, which were represented as follows: The high-intensity interval training method has a clear effect on improving general endurance and reducing the general body fat percentage among beginners practicing sports.
Keywords: HIIT cardio exercises; general endurance; body fat percentage